Analysis of Factors Associated with the Incidence of Complications in Patients with Acute Post Streptococcal Glomerulonephritis - muzalipah, muzalipah; Muljanto, Selli; Rahman, Galih (Enrichment: Journal of Multidisciplinary Research and Development, 2025)
Post-streptococcal acute glomerulonephritis (PSAGN) is a form of glomerulonephritis that occurs after group A ?-hemolytic Streptococcus infection and is one of the leading causes of renal impairment in children. Although the prognosis is generally good, some patients develop serious complications, such as emergent hypertension, acute renal failure (AKI), congestive heart failure (CHF), and encephalopathy. This study aims to analyze the factors associated with the incidence of complications in PSAGN patients at RSUD Ulin Banjarmasin. This study used a cross-sectional retrospective design with data from the medical records of PSAGN patients treated between January 2022 and September 2024. The results showed that emergency hypertension was significantly associated with edema and high serum creatinine levels. CHF was more common in patients with low albumin levels, while encephalopathy was found to correlate with excess nutritional status, proteinuria, and crisis hypertension. This study underscores the importance of close monitoring of PSAGN patients to detect early risk factors for complications and provide appropriate interventions to reduce morbidity.